Physical decontamination of lupin (Lupinus angustifolius) protein isolates, seeds and flakes: Effects on microbiological status and micellar protein yield. (March 2016) - Melde, Denise; Wiacek, Claudia; Braun, Peggy Gabriele
Abstract: Plant seeds are important food sources. Because of inevitable soil contact seeds harbor a large number of microorganisms, especially spore-forming bacteria who are able to germinate in food products. Micellar lupin ( Lupinus angustifolius ) protein isolates, suitable as fat replacers in foods, may include these bacteria and therefore represent a risk for consumers. To guarantee safe food, these protein isolates were pasteurized (60–80 °C, 2.5–30 min), leading to a 4-log reduction of the microbial count. Nevertheless spore-forming microorganisms remained. To inactivate these bacteria whole lupin seeds and processed raw materials (dehulled seeds, flakes) were decontaminated before protein extraction by physical methods: Ultraviolet (UVC) radiation (20, 60 min), dry heat (60 min, 110–140 °C) and wet heat (autoclaving: 115 °C, 20 min). Protein yield and decontamination performance were investigated. Autoclaving turned out to be unsuitable (up to 50% decrease of protein yield) whereas dry heat at 110 °C and 120 °C resulted in a significant increase for all raw materials. Best results concerning protein yield and decontamination performance were obtained by a dry heat treatment (130 °C) for dehulled seeds and flakes and by UVC radiation (60 min) for whole seeds, dehulled seeds and full-fat flakes. Highlights: Ultraviolet (UVC) radiation and dry heat are suitable for seed decontamination. Results of UVC decontamination depend on method of seed preparation. UVC radiation of lupin seeds and flakes does not affect extractable protein yield. Dry heat treatment (110–130 °C) of lupin flakes increases protein yields. Lupin seeds and flakes are more sensitive to wet heat versus dry heat at 120 °C.